Comparison of Preoperative Inflammation-based Prognostic Scores in Patients With Colorectal Cancer. Issue 3 (March 2018) - Suzuki, Yoshiyuki; Okabayashi, Koji; Hasegawa, Hirotoshi; Tsuruta, Masashi; Shigeta, Kohei; Kondo, Takayuki; Kitagawa, Yuko
Abstract : Objective: To evaluate the prognostic impact of the systemic inflammation score (SIS) in colorectal cancer (CRC) patients in comparison with a conventional inflammation-based score, the modified Glasgow Prognostic Score (mGPS). Summary Background Data: The SIS, which is calculated based on the preoperative serum albumin level and lymphocyte-to-monocyte ratio, is a reported prognostic marker in clear-cell renal cell carcinoma. However, the utility of the SIS in CRC remains unclear. Methods: The study involved 727 CRC patients who underwent curative resection between September 2005 and December 2011. The prognostic impact of SIS and mGPS was evaluated using survival analyses. The prognostic impact of each score was compared visually by means of time-dependent receiver operating characteristics analysis. Results: The median age of the patients was 67 (interquartile range: 58–75) years. The TNM stage distribution was stage I, 29.8%; stage II, 33.6%; stage III, 30.3%; and stage IV, 6.3%. The median follow-up period was 5.61 years (interquartile range: 4.24–7.06). Multivariate analysis revealed that an increased SIS and mGPS were independent prognostic factors (SIS: P = 0.018; mGPS: P = 0.005, respectively). The time-dependent receiver operating characteristics curve of the SIS was superior to that of the mGPS throughout the observation period. The estimated area under the curve (AUC) of the SIS was significantly higher than that of the mGPS (7-yr survival: SIS 0.673, mGPS 0.605, P = 0.030). Conclusions: The SIS is a novel prognostic factor in CRC patients. Additionally, the SIS is an alternative inflammation-based biomarker, which may improve the prediction of clinical outcomes. Abstract : Supplemental Digital Content is available in the text